The challenge of developing creativity - Prof Muhammad Yunus (Indonesia Prime, 2018)
The ability of thinking Creativity, change, find and create something. Term kThe world of science and the general public reativitas are common terms. In fact, creativity and human life are two different things, but the parcel has an impact and is closely correlated. Life and civilization will stagnate without vacuum and creativity. Creativity always shows up The Rhythm Space and time with proper thinking and human needs